FIBRE QUALITIES OF BOLLS DEVELOPED UNDER DIFFERENT DAY AND NIGHT TEMPERATURES IN VARIOUS PAKISTANI COTTON VARIETIES AND MUTANT STRAINS - Bandesha, A. A.; Aslam, M.; Ishaque, W.; Haq, M. A. (The Nucleus, 2020)
Four commercial cotton varieties NIAB-78, B-557, SLH-41, MNH-93 and four advanced mutants strains N-82, L-21, L-25 and M-626 were used to study the effect of temperature on fibre quality during boll developing stage. The results showed that varieties differed significantly in all fibre quality parameters. There was significant increase in fibre length under medium temperature range while significant increase in fibre strength and highly significant increase in Micronaire values and maturity index under high temperature conditions. The medium temperature range (24.5 to 30.6ï‚°C) seemed to be ideal for cotton fibre development.